The struggle between cash and electronic payments - Zsófia Pintér; Mónika Zita Nagy; Katalin Tóth; József Varga (Economies, 2022)
The assessment of consumer behavior regarding the choice of financial instruments may be extremely important in the near future, since the fight between cash and electronic money has reached a turning point, and electronic payments are slowly defeating cash. On one hand, in the long term, this possible separation threatens sustainable development goals, and on the other hand, financial awareness can affect the number of purchases and savings. In a survey of 499 people, we examined the reasons behind their decisions, with a particular focus on financial awareness. The result shows that the vast majority of Hungarian consumers are not yet ready to fully accept electronic payments. It can be stated that financial awareness is not present at all in one-fifth of respondents, and one-third are influenced by habituation in everyday shopping situations, which indicates a lack of financial awareness. Based on our results, we have concluded that our consumers still find it difficult to abandon cash payments. Financial awareness needs to be improved in parallel with the Hungarian government's strategy to reduce the use of cash.
Keywords: 330; cashless society; consumer survey; digitalization; financial awareness; means of payment; sustainability; waste